Umiranja jelke (Abies alba Mill.) v Sloveniji - Čufar, Katarina (Zbornik gozdarstva in lesarstva, 1997)
Investigations on silver fir (Abies alba Mill.) decline in Slovenia conducted by the Chair of Wood Science directed by Torelli are reviewed. The investigations completed within 1985-1996 include the monitoring of tree condition using an electrical resistance (ER) measuring method with anatomical and physiological interpretation of the ER readings, studies on growth reduction, and phenology, reproductive growth, development of epicormic branches, wood miosture content and wood quality, the frequency of slime cells in the bark and traumatic resin canals in wood, and the responses of wood and bark to mechanical wounding
Keywords: anatomija lesa; gozdarstvo; gozdovi; jelka (botanika); propadanje gozdov; rast